Determinants of Employee Productivity in Public Institutions: Integrating Recruitment, Motivation, and Organizational Factors - Faizal Rachman; Hapzi Ali (Jurnal Ilmu Multidisiplin, 2025)
Employee productivity in public institutions is a key determinant of organizational effectiveness. This article provides a systematic analysis integrating Human Capital Theory, Expectancy Theory, Public Service Motivation (PSM), Transformational Leadership Theory, and High-Performance Work Systems (HPWS). The study aims to build a comprehensive conceptual model explaining how competency-based recruitment, intrinsic–extrinsic motivation, organizational culture, digital transformation, and leadership influence employee competence and sustainable productivity in BPJS Ketenagakerjaan. The results of the literature synthesis show that intrinsic motivation, mission-driven orientation, competency alignment, and collaborative leadership practices are the strongest predictors of long-term employee productivity. This article contributes to strengthening strategic HRM design in public-sector organizations.